Paulo Freire e Lucáks para a constituição de uma proposta com vistas à emancipação humana e à conscientização na promoção da saúde na educação física escolar - Gomes, Michell Plattini Nascimento (2019)
Qualitative and bibliographical research on school physical education related to health promotion, with focus on empowerment and awareness. The state of the art produced on health in school physical education of the last five years, according to Bracht et al. (2011), in periodicals of the area that produced the most about school physical education, indicated a small number of articles that address this theme. This, for the purpose of discussion, is organized in: health and physical education School; pedagogical dimension; practices and physical activity / health. A rescue of the approach on health in Physical Education in the school and in society is made, emphasizing that health often behaves like agent of social control and reproduction of the capitalist ideology. In the last few topics, Freirean categories, such as awareness and empowerment, approach the study in a perspective of theoretical formulation for a broader, progressive, critical and self-critical approach to health by Physical School Education, which is intended to collaborate in the building of a socialist society. It is highlighted in this proposal, the non-detachment of the social being from the biological being, understanding that it is a complex being.